Description and Outcomes of A Buprenorphine Maintenance Treatment Program Integrated within Prevention Point Philadelphia, An Urban Syringe Exchange Program. Issue 2 (April 2018) - Bachhuber, Marcus A.; Thompson, Cole; Prybylowski, Ann; Benitez, José; Mazzella, Silvana; Barclay, David
Background: Syringe exchange programs are uniquely positioned to offer treatment services to interested clients. Prevention Point Philadelphia recently expanded to offer buprenorphine maintenance treatment through its Stabilization, Treatment, and Engagement Program (STEP). Objective: To describe the STEP model of care and report treatment outcomes. Methods: Retrospective chart review of patients enrolled in STEP (October 2011-August 2014). Our main outcome measure was time retained in treatment, defined as time from treatment initiation to treatment failure. Secondary outcome measures were buprenorphine and opiate use, from urine toxicology screens. We analyzed retention in treatment using Kaplan-Meier survival estimates; patients who remained in treatment at the end of the study period were censored on that day. For buprenorphine and opiate use, we calculated the percentage of patients who were positive for buprenorphine and opiates in each month of treatment. Results: Of the 124 patients enrolled in STEP, the median age was 41 (range 21 to 63) and 80% reported injection heroin use. Comorbidities were common: 33% had HIV infection, most reported anxiety (78%) or depression (71%), and 20% were homeless. The most common program outcomes were unplanned self-discharge ( n = 29; 23%), incarceration ( n = 20; 16%), and administrative discharge ( n = 19; 15%). The percentage of patients retained in treatment at 3, 6, 9, and 12 months was 77%, 65%, 59%, and 56%, respectively. Among those retained, the percentage with a positive buprenorphine screen at 3, 6, 9, and 12 months was 88%, 100%, 96%, and 95%, respectively. The percentage with a positive opiates screen was 19%, 13%, 17%, and 16%, respectively. Conclusions: With a program that blended organizational and community resources, retention in buprenorphine maintenance treatment was comparable to retention rates reported from other settings. Further research should directly compare treatment outcomes in syringe exchange program-based settings versus primary care and specialty settings.